How to coach: A review of theoretical approaches for the development of a novel coach education framework - Smith, K.; Burns, C.; O`Neill, C.; Duggan, J. D.; Winkelman, N.; Wilkie, M.; Coughlan, E. K. (International Journal of Sports Science & Coaching, 2023)
Coaching behaviours often derive from sporting traditions, instinct and previous experiences. Practitioners tend to follow traditional, inherited methods rather than adopt new evidence-based approaches associated with athlete development. This article reviews literature relating to theoretical constructs of a novel coach education framework (CEF) developed by the Irish Rugby Football Union. The three constructs included are: self-determination theory (SDT), explicit learning theories (ELT) and implicit learning theories (ILT). A total of 82 publications met the inclusion criteria (SDT: n = 18, ELT: n = 28, ILT: n = 36). This review supports the efficacy of these constructs in isolation for promoting effective coaching practices and provides a justification for future implementation of the framework and its evaluation. This framework may have the potential to address a shortfall in current coach education formats, which have traditionally focused on What content should be used for athlete development as opposed to How practitioners can coach more effectively.